Pemanfaatan Foto Udara Format Kecil Untuk Pendataan Objek Pajak Bumi Dan Bangunan (Studi Kasus di Wilayah Kerja Kantor Pelayanan PBB Sleman) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
The use of small-format aerial photo in data collection of property tax objects has not been optimum yet. For narrow areas that do not need highly accurate data, the small-format aerial photos can be used as an alternative solution. This research is to study the use of small-format aerial photos in the measurement of land parcels for property tax data collection. This research used two different techniques to small-format aerial photos. Firstly, a controlled mosaic of photo image was produced from an uncontrolled mosaic of photo images which were corrected geometrically applying the polynomial transformation model order 1, order 2, and order 3. Secondly, a controlled mosaic of photo images was produced from two single photo images corrected geometrically with the same polynomial transformation model. The ground control point was obtained from point identification on an ortho photo map scale 1 : 5000. The differences of land parcel areas between the data obtained from the photo image mosaic digitation and the data available as the attribute data in the Property Tax Information and Management System (SISMIOP) were computed. The differences allowed between them are less than 10%. The average values of RMSE produced from the first technique was 7.606 m, whereas that of RMSE produced from the second technique was 8.311 in for the photo 1 and 6.485 m for the photo 2. The mosaic of photo images obtained from the first technique with the polynomial transformation order 1 produced the smallest average of area differences, which was 7.20 m2, or about 1.59%. The mosaic of photo images corrected geometrically applying the polynomial transformation order 1 is suitable for flat areas, because it produced the smallest area differences compared with the SISMIOP data. The small-format aerial photos can be used to measure the land parcel areas in data collection for property tax purposes, but in the implementation it needs verification to identify and determine the boundaries of land ownerships.